Ambient Ionization Mass Spectrometry for Point-of-Care Diagnostics and Other Clinical Measurements. (6th January 2020) - Ferreira, Christina R; Yannell, Karen E; Jarmusch, Alan K; Pirro, Valentina; Ouyang, Zheng; Cooks, R Graham
Abstract: BACKGROUND: One driving motivation in the development of point-of-care (POC) diagnostics is to conveniently and immediately provide information upon which healthcare decisions can be based, while the patient is on site. Ambient ionization mass spectrometry (MS) allows direct chemical analysis of unmodified and complex biological samples. This suite of ionization techniques was introduced a decade ago and now includes a number of techniques, all seeking to minimize or eliminate sample preparation. Such approaches provide new opportunities for POC diagnostics and rapid measurements of exogenous and endogenous molecules (e.g., drugs, proteins, hormones) in small volumes of biological samples, especially when coupled with miniature mass spectrometers. CONTENT: Ambient MS-based techniques are applied in diverse fields such as forensics, pharmaceutical development, reaction monitoring, and food analysis. Clinical applications of ambient MS are at an early stage but show promise for POC diagnostics. This review provides a brief overview of various ambient ionization techniques providing background, examples of applications, and the current state of translation to clinical practice. The primary focus is on paper spray (PS) ionization, which allows quantification of analytes in complex biofluids. Current developments in the miniaturization of mass spectrometers are discussed. SUMMARY: Ambient ionization MS is an emerging technology in analytical and clinical chemistry. With appropriate MS instrumentation and user-friendly interfaces for automated analysis, ambient ionization techniques can provide quantitative POC measurements. Most significantly, the implementation of PS could improve the quality and lower the cost of POC testing in a variety of clinical settings.